Chapter Supportare e accompagnare i processi di autonomia nei settori dell'istruzione e della formazione nell'era digitale - Infante, Pierpaolo (Studies on Adult Learning and Education, 2022)
The COVID-19 pandemic is still impacting education and training systems. Under extremely challenging circumstances, it accelerated digital transformation and triggered rapid, large-scale change. Developments that would otherwise have taken years, were possible in only a few weeks. Today we are facing both challenges and opportunities. This means that we need to help teaching, step up our efforts and gradually move from temporary, emergency-focused distance education to more effective, sustainable and equitable digital education, within the framework of creative, flexible, modern and inclusive education and training. The education and training system is increasingly part of the digital transformation and it can take advantage of the benefits and opportunities of this ongoing change.